2013
DOI: 10.1542/peds.2012-3584
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Link Between Insulin Resistance and Elevated ALT

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Evaluating for elevations in alanine aminotransferase (ALT) is a common screening test for the presence of nonalcoholic fatty liver disease (NAFLD). NAFLD is less common among non-Hispanic blacks. Better predictors of NAFLD are needed to identify individuals in most need of screening. WHAT THIS STUDY ADDS:Relative to other ethnicities, metabolic syndrome and insulin resistance performed poorly at identifying non-Hispanic black adolescents with ALT elevations. The presence of metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…In addition, certain genetic alleles have been associated with an increase in the progression to fibrosis in both adult and pediatric populations. 48,49 Although studies report a preponderance of NAFLD in Hispanic children, compared to non-Hispanic blacks and white children, 50 we did not observe these race/ethnic differences in our predominantly Hispanic population. Our lack of spotting these known race/ethnic differences could be owing to our using predicting equations, rather than liver biopsies.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, certain genetic alleles have been associated with an increase in the progression to fibrosis in both adult and pediatric populations. 48,49 Although studies report a preponderance of NAFLD in Hispanic children, compared to non-Hispanic blacks and white children, 50 we did not observe these race/ethnic differences in our predominantly Hispanic population. Our lack of spotting these known race/ethnic differences could be owing to our using predicting equations, rather than liver biopsies.…”
Section: Discussioncontrasting
confidence: 74%
“…8 The ATP-III criteria also do not account for differences in MetS by race/ethnicity and gender, resulting in MetS underdiagnosis in specific groups, such as non-Hispanic blacks. [9][10][11][12][13][14] This is a concern because non-Hispanic-black individuals have higher rates of T2DM and CVD despite low rates of ATP-III MetS diagnosis. [15][16][17][18][19] The recently developed MetS Severity Score (MetS z score) calculator addresses the epidemiologic limitations of the ATP-III criteria.…”
mentioning
confidence: 99%
“…In addition, despite differences in body fat, Hispanic and nonHispanic black children are more insulin-resistant than non-Hispanic white children. 11,16 A similar study found that children with metabolic syndrome had lower insulin sensitivity when compared with children without any risk factors, 17 possibly representing an important indicator for the development of cardiovascular disease and type 2 diabetes mellitus. 11,17 According to Marzuillo and colleagues, 18 nonalcoholic fatty liver disease (NAFLD) has more than doubled in the last 20 years, mirroring the increase prevalence in childhood obesity and becoming the most common form of liver disease in childhood.…”
Section: Impact Of Obesity On Latino Youthmentioning
confidence: 89%